Is Limb Loss Always Inevitable for Critical Neuro-Ischemic Foot Wounds in Diabetic Patients with End Stage Renal Disease and Unfit for Vascular Reconstructions? - Alexandrescu, Vlad (IntechOpen, 2012)
None